Stability regimes of a dilatant, fluid-infiltrated fault plane in a three-dimensional elastic solid - Hillers, Gregor; Miller, Stephen Andrew (My University, 2006)
[ 1] We investigate in a systematic parameter space study dilatant effects on slip evolution of a fluid-infiltrated fault in the continuum limit. The fault is governed by rate-and state-dependent friction and an empirical law for porosity evolution. We focus on the response of systems as a function of fluid-related parameters, such as the degree of overpressurization, dilatancy and diffusivity. This study emphasizes the exploration of the parameter space for homogeneous along-strike properties to investigate the evolution of spatiotemporal slip depending on hydromechanical processes. Three types of responses emerge. First, system-wide unstable stick-slip develops for drained conditions, and for undrained conditions if mechanisms leading to an increase in pore space are less effective. The critical stiffness depends on hydraulic diffusivity and dilatancy, which is shown to correspond with interevent times of simulated stick-slip events. During instabilities the evolution of hydraulic variables differ significantly between drained and undrained conditions. Second, stable creep is a result of dilatant processes. Third, systems situated in transitional stability regimes develop nonuniform slip pattern in space and time, revealing a possible explanation for rupture termination and observed stable afterslip. Although these patterns are produced by models located in transition zones of the parameter space, the occurrence of heterogeneous slip evolution is persistent for an extensive range of parameter values. Since transition zones contain an broad range of plausible conditions in the crust, they do not represent extreme cases.